Kajian tentang Efek Garam terhadap Kinetika Transfer Co(II) dalam Sistem Dwi-Fasa Air/Asam di-(2-etilheksil)fosfat - Hendrawan Hendrawan; Yaya Sonjaya; Hernani Hernani (Institut Teknologi Bandung, 2004)
The study of salt effect on kinetic of Co(II) transfer in aqueous/di-(2-ethylhexyl)phosphoric acid (D2EHPA) system has been performed using the technique of rotating membrane cell (RMC). Co(II) solutions in various conditions of aqueous phase were transferred into solution of di-(2-ethylhexyl)phosphoric acid in n-dodecane, as an organic phase, at various speeds of rotation. The result shows that the transfer of cobalt from aqueous into organic phase (D2EHPA) follows the transfer model of mass transfer with chemical reaction (MTWCR). The diffusion rate of complexed cobalt in the aqueous phase is the rate determining step. Higher ionic strenggt in bulk aqueous, lower affinity of aqueous solution to cobalt. The affinity of aqueous solution to cobalt becomes smaller as the ionic strength in the bulk aqueous increase.